2016
DOI: 10.1007/s11661-016-3748-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ga and Sn Additions on the Creep Strength and Oxidation Resistance of Near-α Ti Alloys

Abstract: The effects of Ga and Sn additions, with an almost constant value regarding Al equivalence, on the creep properties and oxidation resistance of the near-a Ti alloy Ti-5Al-4Zr-1Mo were investigated. The creep strain rate increased due to the replacement of Sn with Ga, which was accompanied by an increase in the volume fraction of primary equiaxed a phase. In addition, the replacement of Sn with Ga decreased the activation energy of the steady-state creep rate for the similar volume fraction of the equiaxed a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Hence, a small amount of Al decreases the oxidation resistance of TA29 alloy. As for the segregation of Sn at the oxide-substrate interface, on the one hand, it increases the vacancy concentration in the alloy, promoting the diffusion of Ti atoms in the alloy; on the other hand, it reduces the adhesion between the oxide scale and the substrate, prompting the oxide scale to peel off [38,39,40]. Both intensify the reaction between Ti and O and decrease the oxidation resistance of the alloy, thus Sn is detrimental to the oxidation resistance of TA29 alloy.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a small amount of Al decreases the oxidation resistance of TA29 alloy. As for the segregation of Sn at the oxide-substrate interface, on the one hand, it increases the vacancy concentration in the alloy, promoting the diffusion of Ti atoms in the alloy; on the other hand, it reduces the adhesion between the oxide scale and the substrate, prompting the oxide scale to peel off [38,39,40]. Both intensify the reaction between Ti and O and decrease the oxidation resistance of the alloy, thus Sn is detrimental to the oxidation resistance of TA29 alloy.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional near-alpha Ti alloys are strengthened by fine alpha2 phase with DO 19 structure and intermetallic silicides [7][8]. Up to now, numerous works were focused on the influence of alpha stabilizing alloying elements such as Ga, Sn, Hf and Zr on the high temperature mechanical properties of the near-alphaa titanium alloys [9][10]12]. These studies demonstrated that the solid solution strengthening and the formation of a 2 phase are effective in improving high temperature strength, but degrade the ductility of the material [10][11] probably due to the lower symmetry of its DO 19 crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, numerous works were focused on the influence of alpha stabilizing alloying elements such as Ga, Sn, Hf and Zr on the high temperature mechanical properties of the near-alphaa titanium alloys [9][10]12]. These studies demonstrated that the solid solution strengthening and the formation of a 2 phase are effective in improving high temperature strength, but degrade the ductility of the material [10][11] probably due to the lower symmetry of its DO 19 crystal structure. The effect of silicon addition was also extensively studied to increase high temperature tensile and creep strength of near-a and a+b titanium alloys [9,[13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that these mechanical properties are also dependent on factors of microstructure morphology such as the volume fraction and size of equiaxed α, the thickness of lamellar, etc. Some authors have shown that creep strength is strongly dependent on the volume fraction of equiaxed α in the bimodal microstructure of Ga and/or Sn added near-α alloys with an almost constant value of Al equivalence [9]. In this study, the volume fraction of equiaxed α was set to be similar in the bimodal microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work showed that room temperature tensile elongation drastically decreased at around 9 to 11 of Al equivalence for a bimodal microstructure of multi-component Ti alloys produced at the National Institute for Materials Science (NIMS) in Japan (for examples, see Kitashima et al [6][7][8][9]). In addition, the minimum creep strain rate decreased with increasing Al equivalence especially between 9 and 11 of Al equivalence due to the formation of α 2 precipitate [8].…”
Section: Introductionmentioning
confidence: 99%